Analisis Isi Mengenai Kekerasan Seksual pada Film Like & Share - Safitri, Nur Aida; Nurlita, Ita (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2024)
Currently, films have educational capabilities, namely the use of films in the world of education, to be able to convey messages to the audience. One film that has a message about the issue of sexual violence in Indonesia is the film titled "Like & Share". This film conveys many moral messages, thus depicting the situation regarding sexual violence. Therefore, the aim of this research is to determine the content analysis of sexual violence in the film "Like & Share" using a quantitative descriptive content analysis method. The results of the discussion include:(1) verbal violence with indicators such as swearing, threatening, coercing, and seducing, (2) physical violence with indicators such as rape, demeaning facial expressions, abuse, and poking, (3) gender-based cyber violence with indicators such as video spreading, photo spreading, voice pornography, child grooming, and cyberbullying,  (4) Psychological violence with indicators such as suicide, self-isolation, uncontrolled emotions, and loss of self-confidence.